Political Participant Psychology of Baghdad Governorate Citizens (Journal Of Educational and Psychological Researches, 2013)
Psychological studies expanded very much, but the researchers forgot very important subjects such as Political participant, and they put their efforts in reading resources to try insuring its results, or to applying it in logic environment and its different Cultures from our Culture in its Values, Criterion, and Attitudes that use their results more difficult. Despite of research movement expansion, but critic was still especially in Political Psychology field, and may be took thritically from researches, and they remote from it practically, and this study a sereace try to put a practical principle that our society need it especially which we practice the Political participant every four years, and we practice it in our departments in College, or in the University, and may be practice with our close friends. May be the most subjects that unique to study it in Psychological field, it is the subject correlate with general opinion measure. And that correlate with people lead, and how they think when they choice the candidate in any Electional process.Formal tries in Egypt from Fouad Thaiab 1970 to know woman writhe in election, and candidate, and why she did not participate in election. Moreover, which Nimaat Fouad tried in 1970 to study the personality of Egyptian woman?This study open door to the researches because the problems which faced the researcher when try to study this kind of subject. May be the subject's importantin sheds lights on most people attitude to elect a candidate, or favorite a party, put its important to the political parties, and which sections of society towered in their movements, and who elect to it. This issues correlate with stop – move conflict to the Electional program of a party, and who it is correlate with people needs, and its propaganda, and effect in the elector, and what it try to arrive to the people mind to let them agree with its content.